Potensi Arang Aktif Kulit Durian sebagai Produk Usaha di Bidang Sanitasi - Mualim, Mualim; Marwanto, Andriana; Adeko, Riang (Jurnal SOLMA, 2024)
Background: Entrepreneurship is a trait that can be seen in the actions of a person or institution and is defined as the attitude and ability to produce something that is unique, innovative, and beneficial to others. Students' interest in becoming entrepreneurs and applying their knowledge to opening a business is very low. So, efforts are needed to develop entrepreneurship in the field of sanitation by making activated charcoal products from durian skin. The aim of this activity is to foster entrepreneurial character in the sanitation sector and increase understanding and skills in making durian peel activated charcoal. Method: The methods that will be applied include: (1) Increasing entrepreneurial knowledge carried out through counseling and training activities to develop entrepreneurial character (2) Assistance in making activated charcoal from durian skin. Result: The result of this activity is an increased understanding of entrepreneurship in the field of sanitation and producing activated charcoal products from durian skin. Conclusion: The conclusion of this community service activity is to produce durian skin activated charcoal products as a form of business opportunity in the sanitation sector.